Observed Teleconnections in Northern Winter: Subseasonal Evolution and Tropical Linkages ... - Baxter, Stephen Robert (Digital Repository at the University of Maryland, 2016)
Teleconnections refer to the climate variability links between non-contiguous geographic regions, and tend to be associated with variability in both space and time of the climate’s semi-permanent circulation features. Teleconnections are well-developed in Northern winter, when they influence subseasonal-to-seasonal climate variability, notably, in surface temperature and precipitation. This work is comprised of four independent studies that improve understanding of tropical-extratropical teleconnections and their surface climate responses, subseasonal teleconnection evolution, and the utility of teleconnections in attribution of extreme climate events. After an introduction to teleconnection analysis as well as the major teleconnection patterns and associated climatic footprints manifest during Northern winter, the lagged impact of the Madden-Julian Oscillation (MJO) on subseasonal climate variability is presented. It is found that monitoring of MJO-related velocity potential anomalies is sufficient to ...